2012
DOI: 10.1007/s00167-012-2093-4
|View full text |Cite
|
Sign up to set email alerts
|

The effect of magnesium added to levobupivacaine for femoral nerve block on postoperative analgesia in patients undergoing ACL reconstruction

Abstract: The addition of magnesium to levobupivacaine prolongs the sensory and motor block duration without increasing side effects, enhances the quality of postoperative analgesia and increases patient satisfaction; however, the addition of magnesium delays the time to first mobilisation and decreases rescue analgesic requirements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
27
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 19 publications
4
27
0
Order By: Relevance
“…Numerous studies in the orthopaedic and anesthesia literature have looked at their efficacy compared with other modalities of postoperative pain management. 12,13,21,26,27,32 Advantages of FNB cited by these studies include lower visual analog scale (VAS) scores for pain at rest and with movement during the immediate postoperative period. 10,15,28 Other studies have shown no significant difference in pain control, side effects, opioid consumption, and readiness for discharge between FNB and local infiltration anesthesia or multimodal anesthesia.…”
Section: -In-5mentioning
confidence: 99%
“…Numerous studies in the orthopaedic and anesthesia literature have looked at their efficacy compared with other modalities of postoperative pain management. 12,13,21,26,27,32 Advantages of FNB cited by these studies include lower visual analog scale (VAS) scores for pain at rest and with movement during the immediate postoperative period. 10,15,28 Other studies have shown no significant difference in pain control, side effects, opioid consumption, and readiness for discharge between FNB and local infiltration anesthesia or multimodal anesthesia.…”
Section: -In-5mentioning
confidence: 99%
“…It was shown to be effective as a postoperative analgesic in orthopedic surgery (7,8). The analgesic property of magnesium is associated with inhibition of the N-methyl-D-aspartate (NMDA) receptor and modulation of calcium channels (9). Furthermore, its addition to local anesthetics prolongs anesthesia duration and maximizes their effects (10,11).…”
Section: Introductionmentioning
confidence: 99%
“…A study by Ekmekci et al (13) showed that addition of magnesium to levobupivacaine prolongs the sensory and motor block duration without increasing side effects, enhances the quality of postoperative analgesia and increases patient satisfaction; however, the addition of magnesium delays the time to first mobilisation and decreases rescue analgesic requirements. Our study shows similar effect in prolongation of post-operative analgesia without increase in adverse effects.…”
mentioning
confidence: 99%